The impact of socioemotional wealth on household net worth and subjective quality of life in the family farm business: an application of the REI model - Zimmerman, Lloyd G. (Kansas State University, 2020)
Sustainable family farming depends on achieving both financial and nonfinancial goals of the family and business systems. The purpose of this study was three-fold: (a) to advance an understanding of socioemotional wealth (SEW) measurements, (b) to better understand farm family household net worth and subjective quality of life in relationship to SEW and return on business equity, and (c) to examine the generational stage of family farm ownership and farm business asset size as moderators between family farm socioemotional wealth and return on business equity. Data for this cross-sectional study were obtained from the National Family Business Survey (NFBS) 1997 panel study, conducted by the National Information Management & Support System (NIMSS). The current study applied the REI model of SEW proposed by Hauck et al. (2016) to operationalize socioemotional wealth as a multi-dimensional construct. Findings of the current study revealed no significant relationship between SEW — as measured using the REI model — and farm family household net worth. However, return on business equity was found to be significantly and negatively associated with farm family household net worth. This result is not supported in the literature. Furthermore, two of the three REI dimensions (i.e., emotional attachment of family members and identification of family with the business) were found to be significantly and positively associated with subjective quality of life in family farming. This result is partially supported in the literature. Results of the present study indicated no significant relationship between return on business equity and subjective quality of life (p < 0.05). Also, generational stage of family farm ownership and farm business asset size were not found to moderate the relationship between family farm socioemotional wealth and return on business equity. Future directions for research and implications for policymakers, educators, and researchers were discussed.
Keywords: Socioemotional wealth; Family farm business; Farm family; Personal financial planning; Family business